The Effect of Discovery Learning on the Critical and Creative Thinking Abilities of Grade IV Elementary School Students - A’an Novita Rizky; Toto Nusantara; Intan Sari Rufiana (Journal of Educational Sciences, 2026)
Critical and creative thinking skills play an important role in supporting students' learning success in elementary school. The observation results show that the learning process is still dominated by conventional learning models, so it tends to be less interesting and has an impact on low critical and creative thinking skills in mathematics learning. Based on these problems, this study aims to determine the effect of the Discovery Learning model on the critical and creative thinking skills of fourth-grade elementary school students. The method used is a quasi-experimental design with a non-equivalent control group design. The sample consisted of 50 students divided into two groups . The experimental group used the Discovery Learning model and the control group followed the conventional learning model. The instrument used was a descriptive test that has been tested for validity and reliability. Data analysis was carried out through normality tests, homogeneity tests, and hypothesis testing using the Independent Sample t-Test. The results of the study show There were significant differences between the two groups. The experimental group demonstrated improved critical and creative thinking skills in mathematics learning. These findings indicate that Discovery Learning is effective in improving students' critical and creative thinking skills.